MiRNAs detection in equine plasma by quantitative polymerase chain reaction for doping control: Assessment of blood sampling and study of eca‐miR‐144 as potential erythropoiesis stimulating agent biomarker. Issue 5 (3rd May 2021) - Loup, Benoit; André, François; Avignon, Justine; Lhuaire, Marion; Delcourt, Vivian; Barnabé, Agnès; Garcia, Patrice; Popot, Marie‐Agnès; Bailly‐Chouriberry, Ludovic
Abstract: Short half‐life doping substances are, quickly eliminated and therefore difficult to control with traditional analytical chemistry methods. Indirect methods targeting biomarkers constitute an alternative to extend detection time frames in doping control analyses. Gene expression analysis (i.e., transcriptomics) has already shown interesting results in both humans and equines for erythropoietin (EPO), growth hormone (GH), and anabolic androgenic steroid (AAS) misuses. In humans, circulating cell‐free microRNAs in plasma were described as new potential biomarkers for control of major doping agent (MDA) abuses. The development of a quantitative polymerase chain reaction (qPCR) method allowing the detection of circulating miRNAs was carried out on equine plasma collected on different type of tubes (EDTA, lithium‐heparin [LiHep]). Although analyzing plasma collected in EDTA tubes is a standard method in molecular biology, analyzing plasma collected in LiHep tubes is challenging, as heparin is a reverse transcription (RT) and a PCR inhibitor. Different strategies were considered, and attention was paid on both miRNAs extraction quality and detection sensitivity. The detection of endogenous circulating miRNAs was performed and compared between the different types of tubes. In parallel, homologs of human miRNAs characterized as potential biomarkers of doping were sought in equine databases. The miRNA eca‐miR‐144, described as potential erythropoiesis stimulating agents (ESAs) administration candidate biomarker was retained and assessed in equine post‐administration samples. The results about the qPCR method development and optimization are exposed as well as the equine miRNAs detection. To our knowledge, this work is the first study and the proof of concept of circulating miRNAs detection in plasma dedicated to equine doping control. Abstract : miRNAs detection in equine plasma as potential doping biomarkers in both EDTA and lithium heparin blood samples.